Konsep Produksi Dalam Ekonomi Islam - Anggraini, Dwi; Salsabila, Zhafirah (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Production is one of the important things in economic activity. The purpose of production is to provide goods and services that can provide maximum benefits for consumers to meet their needs and to full fill the facilities of social activities and worship of God. Even though the main purpose of producing is to provide benefits and gain a lot of profit, Islam does not prohibit it as long as it is within the goals and Islamic law. In Islam, carrying out production activities must be based on Islamic values, namely, they must not conflict with religion, soul, reason, and things that can lead to harm. Production priority must be in accordance with priority needs, namely dharuriyyat, hajyiyat and tahsiniyat.